Influence of field beans (Vicia faba L.) on yield and environmental footprint of following spring barley (Hordeum vulgare L.) crops - Umut Kartal; Colm Duffy; Sophie Saget; Frances Sandison; Andrew Christie; Cathy Hawes; Becky Howard; Roger Vickers; Dimitrios Savvas; David Styles; Pietro P. M. Iannetta (Plant and Soil, 2026)
Background and Aims The urgent need to reduce greenhouse gas emissions has increased interest in legume-based cropping systems. Among the various crop-legume species available, the cool-season species Vicia faba L. (cv. minor; field beans) has attracted significant interest. Assessment of the environmental impact reduction of field beans in a crop-sequence (rotation) is understudied. Methods Data from a long term (2009–2023) field bean experimental platform (the Centre for Sustainable Cropping, CSC; James Hutton Institute, Scotland, UK) were analysed using attributional life cycle assessment (aLCA). This focused on elaborating the impacts of a spring field bean to spring barley ( Hordeum vulgare L.) cropping sequence compared with a spring barley to spring barley cropping sequence. Results Field beans decreased the environmental impact of spring barley production in four of the five two-year crop-sequence periods, with mean impact reductions of approximately 25% across sequences. Spring barley grain yields tended to increase following field beans under drought conditions (2022). A combined index analysis indicated that humidity, maximum temperature, and previous field bean yields were the strongest determinants of spring barley production. Conclusions The integration of field beans to cereal-dominated rotations may be of interest to major industries who seek to improve value chain sustainability, whilst ensuring crop-sequence yields are climate-impact resilient.

Environmental assessment of anaerobic digestion within net-zero and policy-aligned AFOLU sector futures - Pedram Vousoughi; Andres Martinez Arce; George Bishop; Daniel Henn; Colm Duffy; David Styles; Kenneth A. Byrne (Journal of Cleaner Production, 2026)

Exploring the frontier of bovine protein production within territorial net zero emission targets - Daniel Henn; Colm Duffy; James Humphreys; James Gibbons; Emma Buckley; Kenneth A. Byrne; David Styles (Science of The Total Environment, 2025)

GeoGOBLIN: A catchment-scale land balance model for assessment of climate mitigation pathways considering environmental trade-offs for multiple impact categories - Colm Duffy; Daniel Henn; David Styles; Gregory G. Toth; Remi Prudhomme; Pietro P.M. Iannetta; Ken Byrne (Environmental Modelling & Software, 2024)

Cattle production strategies to deliver protein with less land and lower environmental impact - Daniel Henn; Colm Duffy; James Humphreys; James Gibbons; Kenneth A. Byrne; David Styles (Journal of Environmental Management, 2024)

Improved representation of cattle herd dynamics for bio-physical modelling of pathways to a climate neutral land sector - Daniel Henn; James Humphreys; Colm Duffy; James Gibbons; David Styles (Agricultural Systems, 2023)

Optimising sustainability: Circular pathways for Scotch Whisky distillery co-products - Colm Duffy; David Styles; Isabel Schestak; Kenneth Macgregor; Frances Jack; Daniel Henn; Kirsty Black; Pietro P.M. Iannetta (Journal of Cleaner Production, 2023)

Agroforestry contributions to smallholder farmer food security in Indonesia - Colm Duffy; Gregory G. Toth; Robert P. O. Hagan; Peter C. McKeown; Syed Ajijur Rahman; Yekti Widyaningsih; Terry C. H. Sunderland; Charles Spillane (Agroforestry Systems, 2021)
Agroforestry has potential for strengthening the climate change resilience of smallholder farmers in Southeast Asia. In Indonesia, the food security challenges faced by smallholders will likely worsen due to climate change impacts. Agroforestry provides and option for strengthening climate change resilience, while contributing to food access, income, health, and environmental stability. To evaluate the evidence for such benefits, this systematic review identifies 22 peer-reviewed articles published between 2000 and 2019 which assess agroforestry’s contributions to food security in Indonesia, mostly in Java or Sumatra. Analysis of the studies indicate that traditional and commercial agroforestry contribute to food security in diverse ways: for example, traditional homegardens offer 20% more dietary diversity than commercial counterparts, while commercial homegardens may contribute up to five times more income. Agri-silviculture contributions fall along a timber versus non-timber forest product continuum that displays a similar tradeoff between diversity and income. Those systems with a commercial focus may receive 54% of their income from a single commodity crop such as coffee, while traditional systems allow greater access to plants with medicinal benefits. Nearly all agroforestry systems offered indirect benefits for food security, such as allowing more off-farm work than traditional agriculture and contributing to environmental stability: users of agroforestry were found by one study to collect 83% less fuelwood from natural forests. One study highlighted that agroforestry options have up to 98% greater net present value (for periods over 30 years) compared to slash and burn style agriculture. However, very few studies of Indonesian agroforestry focused explicitly on financial analysis and food security, indicating the need for further research. Given the similar situations faced by many Southeast Asia countries, our findings contribute to emerging trends throughout the region regarding the relationship between agroforestry and food security.

Drivers of household and agricultural adaptation to climate change in Vietnam - Colm Duffy; Valerien Pede; Gregory Toth; Kevin Kilcline; Cathal O’Donoghue; Mary Ryan; Charles Spillane (Climate and Development, 2021)

Climate smart agriculture extension: gender disparities in agroforestry knowledge acquisition - Colm Duffy; Greg Toth; John Cullinan; Una Murray; Charles Spillane (Climate and Development, 2021)

Constraints to the adoption of fodder tree technology in Malawi - Gregory G. Toth; P. K. Ramachandran Nair; Colm P. Duffy; Steven C. Franzel (Sustainability Science, 2017)